Designing Primers with a Plant Signal Peptide to Enhance the Expression of GBA1 in Transgenic Soybean Plants (Baghdad Science Journal, 2021)
Transgenic plants offer advantages for the manufacture of recombinant proteins with terminalmannose residues on their glycan chains. So plants are chosen as source of pharmaceutical products and forthe development of alternative expression systems to produce recombinant lysosomal enzymes. In thepresent study the sequence of the natural cDNA encoding for the human lysosomal enzymeglucocerebrosidase (GCD) was modified to enhance its expression in soybean plants. The glucocerebrosidasegene signal peptide was substituted with that signal peptide for the Arabidopsis thaliana basic endochitinasegene to support the co-translational translocation into the endoplasmic reticulum (ER), and the storagevacuole. So, targeting signal from tobacco chitinase A, to facilitate GCD trafficking from the ER to thestorage vacuole, appropriate primers were designed containing both an ER and vacuolar targeting signals,(VTS). Those primers were used for PCR amplification of the human GBA gene (Hu-GBA) gene fromconstructed PGEM-GBA plasmid which was cloned in the plant expression vector pCAMBIA1304. Theresulted construct was transported in Agrobacterium tumefaciens strain LBA4404 and was used fortransformation of cotyledon explants. After 5-day of seedling, cotyledons were cut and used as explants.After infection and co-cultivation, hygromycin B was added in selection media as a selective agent for thetransformants cotyledons. The presence of the Hu-GBA transgene in the genomes of transgenic plants wasdetermined by polymerase chain reaction PCR as a band of size1587 bp. The GBA mRNA expression inmodified soybean was detected by qRT-PCR compared with control GBA mRNA.